Short-term effects of ophthalmic topical 0.01% atropine on the ocular surface, pupil size, and subsequent subjective quality of vision in young myopic Chinese adults - Li, Mingze; Chen, Yimeng; Chen, Jiayan; Qin, Guanghao; Li, Liangzhe; He, Wei; Yu, Sile; He, Xingru; Pazo, Emmanuel Eric; Xu, Ling (Frontiers in Medicine, 2024)
Background Daily use of low concentrations of atropine is recommended for children undergoing myopia control therapy. While the benefits of controlling myopia progression have been confirmed, the potential unwanted side effects on the ocular surface, pupil size, and quality of vision following the administration of 0.01% atropine have not been investigated. Objective This single-arm, self-control study aimed to investigate the short-term effects of 0.01% atropine topical eye drop (He Eye Hospital Co., Ltd., Shenyang, China) on pupil size and subjective quality of vision in participants with myopia. Each 3 mL vial of eye drops contains atropine (0.01%), sodium chloride (0.9%), and benzalkonium chloride (0.005%) in an aqueous solution. Methods Thirty-three adults (66 eyes) were recruited for the study. The mean age of the participants recruited for this study was 24.91 ± 3.36 years. This study is registered with Clinical Trials.gov (NCT06071260). Assessments were performed at baseline and 10 h, 14 h, and 18 h following the administration of 0.01% topical atropine drop (TAD). Mesopic pupil diameter (MPD), photopic pupil diameter (PPD), higher order aberration (HOA), non-invasive tear breakup time (NITBUT), tear meniscus height (TMH), tear film lipid layer (TFLL), and Redness score (RS). Subjective assessments included the quality of vision (QoV) and the ocular surface disease index (OSDI) questionnaires. Results Following the use of 0.01% atropine, PPD significantly increased at all the time points (p < 0.001); MPD increased significantly at 10 h and 14 h (p < 0.001 and p < 0.05, respectively). A decrease in TMH and an increase in the OSDI questionnaire scores were observed up to 10 and 14 h, respectively, after using atropine (p < 0.001). Glare (p = 0.004 at 10 h and p = 0.003 at 14 h), blurred vision (p < 0.0001 at 10 h and p = 0.035 at 14 h), and focusing difficulties (p < 0.0001 at 10 h and p < 0.0001 at 14 h) were significantly higher at both 10 h and 14 h after using atropine. No significant changes were observed in the HOA, NITBUT, and RS scores (all p > 0.05) at all time points. Conclusion Decreased TMH, dry eye symptoms, and visual symptoms will likely persist overnight but often diminish within 18 h after using 0.01% atropine eye drops.